Iusque in armis esse. The role of battle in Castilian late medieval dynastic civil wars (Edad Media. Revista de Historia, 2025)
This paper examines the role of battle in three Castilian dynastic civil wars between 1366 and 1479. The particularities of the civil wars that confronted two candidates for the throne made it necessary to adapt the military strategy, favoring pitched engagements over sieges and raids. The honor and public image transmitted were decisive in maintaining alliances and gaining new adherents, underscoring the crucial role of propaganda. Furthermore, in war planning, military logic is argued to be subordinated to economic, socio-political, and cultural conditioning factors.
Keywords: War; Strategy; Propaganda; Castile; Late Middle Ages